Identification of Occupational Injury among the Workers of Selected Cement Industries in Bangladesh - A Case Study - Iqbal, Salma A; Iqbal, Mohammed; Taufiq, Md Zubair; Ahmed, Md Shamim (Journal of Chemical Engineering, 2011)
The paper deals with the identification of occupational injury among workers in selected cement industries of Bangladesh. In this regard, the case study was conducted to extract the overall scenario of the occupational injury. Injury data were collected by using questionnaires from the workers as well as supervisors of four cement industries. The data collected were analyzed in terms of different variables, such as body parts, agent of accident, experience, age, skill, and type of injury. Pareto analysis was then applied to find a pattern of occupational injury among the workers. The study disclosed that arm, leg, hand finger, Eye and head covered 82.81% of total i njury frequency, 76.56% of total injuries by welding, bucket elevator, belt conveyor and weight lifting, low experienced and high experienced workers have 84.38% of total injury frequency, age group of 21-25 and 51-55 have the maximum injury frequency, 78.13% injury occurred by highly skilled and unskilled workers and 79.1% of total injury is temporary disable type injury. The paper also provides specific suggestions followed by some action plans. Keywords injury; accident; workers; safety; cement industry; training. DOI: 10.3329/jce.v25i0.7236 Journal of Chemical Engineering, IEB Vol. ChE. 25, No. 1, December 2010 pp.22-28